KEPERCAYAAN TERHADAP OTORITAS PAJAK SEBAGAI PEMODERASI PENGARUH DETERRENCE FACTORS TERHADAP KEPATUHAN WAJIB PAJAK PRIBADI - Dwi Ratmono; Nur Cahyonowati (Jurnal Akuntansi Indonesia, 2013)
This study examines the role of trust to moderate the relationship between deterrence factors and taxpayer compliance behavior. Their compalince on tax regulation is hypothesized to be determined by three factors i.e. tax audit, tax fine and trust in tax authorities. Economics-of-crime approach predicts that the higher probability of tax audit and tax fine will enhance tax compliance. According to slippery slope theory, the positive relation of tax compliance and its deterrence factors might be stronger if tax payer has a higher trust in legal and taxation system. The field experiment is designed by 2x2x2 between subjects. The participants comprise of 80 personal tax payers in Semarang City. Using ANOVA as statistical analysis, this reseach suggested that tax compliance is more likey to be effectively affected by trust in tax authorities rather than deterrence factor. However, according to univariate analysis, tax audit and tax fine are still important determinants of tax compliance.